Cyclodextrin glycosyltransferase production by the Bacillus sp., subgroup alcalophilus using a central composite design - Blanco, K. C. [UNESP]; de Lima, C. J B [UNESP]; de Oliveira, P. A P L V; Pião, A. C S [UNESP]; Contiero, Jonas [UNESP] (Science Alert, 2009)
Cyclodextrin glycosyltransferase (CGTase) activity was produced by the Bacillus sp., subgroup alcalophilus in a culture medium containing cassava starch. A central composite design and response surface methodology were used to study the influence of carbon source (cassava starch), nitrogen sources (yeast extract and tryptone) and sodium carbonate in the production medium. Assays were performed in 300 mL Erlenmeyer flasks containing 100 mL of production medium maintained in a shaker at 150 rpm at 35±1°C for 72 h of fermentation. The independent variables [0.75% cassava starch, nitrogen sources (0.375% yeast extract and 0.375% tryptone) and 1% Na2CO3] produced an enzyme activity of 96.07 U mL-1.© Academic Journals Inc.
Keywords: Alcalophilus; Bacillus sp.; Cassava starch; Central composite design; Cyclodextrin glycosyltransferase; Enzyme activity; Subgroup; Manihot esculenta